PENGARUH LAMA PERENDAMAN DAGING PAHA ITIK TEGAL (ANAS PLANTYRHYNCHOS JAVANICUS) PADA AIR DINGIN (5-10?C) TERHADAP TOTAL BAKTERI DAN PH - Wilangkara, Ranu; Rahardjo, Agustinus Hantoro Djoko; Widayaka, Kusuma (ANGON: Journal of Animal Science and Technology, 2022)
Background. This study aimed to determine the effect of soaking duck thighs at a cold temperature of 5-10?C on total bacteria and pH. Materials and methods. The research materials used were 20 pieces of commercial duck thigh meat, water, ice cubes, NA media, aquadest, 70% alcohol, buffer solution, 0.85% NaCl. The research method was experimental using a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments given were soaking duck thighs in 5-10?C cold water, R1 for 0 minutes (a moment), R2 for 15 minutes, R3 for 30 minutes, and R4 for 45 minutes. The results of the study of total bacteria obtained an average of R1 of 6.12 x 104 cfu/g, R2 decreased by 4.39 x 104 cfu/g or 17.25%, R3 decreased by 1.24 x 104 cfu/g or 48, 8% and R4 down 2.19 x 103 cfu/g or 59.01%. The number of bacteria decreased linearly following the line equation Y = 4.74 - 0.03 X with a coefficient of determination (R2) = 62.39%. The average total bacteria obtained was 2.9 x 104 cfu/g. Results. The results of the pH study obtained an average R1 of 6.90; R2 of 7.19; R3 is 7.36 and R4 is 6.45. The average pH obtained is 6.97. Conclusion. The results of the analysis showed that the duration of soaking duck thighs in cold water of 5-10?C had a very significant effect (P<0.01) on total bacteria and had no significant effect (P>0.05) on pH. In conclusion, soaking duck thighs at a cold temperature of 5-10?C for up to 45 minutes can reduce the number of bacteria by 59.01% and the pH value remains constant.